Analysis of The Influences of Leadership, Organizational Culture, Competence and Infrastructure on The Non-Formal Education Organization Performance of The Education Office of Tambrauw Regency – Southwest Papua Province - Suruan, Jenni Ludia; Jan, Arrazi Hasan; Pandowo, Merinda H. Ch. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This research is to analyze the effect of leadership, organizational culture, competency and infrastructure on the performance of non-formal education organizations at the education office in Tambrauw Regency, Southwest Papua Province, simultaneously or partially. The method in this study is a quantitative method using 90 people as a research sample. Based on the results of the study, it shows that simultaneously the variables of leadership, organizational culture, competence, and infrastructure have a positive relationship and significantly influence the performance of non-formal education organizations in the Education Office in Tambrauw Regency. Partially the variables of leadership, organizational culture, competence.